Performance of simple concrete pipes produced with the incorporation of rubber tires - Akasaki, J. [UNESP]; Fioriti, C. [UNESP]; Queiroz, R. [UNESP]; Fugii, A. [UNESP]; Pinheiro, J. [UNESP] (Pontificia Univ Catolica Chile, Dept Ingenieria & Gestion Construccion, 2016)
In this work we have studied the performance of simple concrete pipes produced with the incorporation of rubber tires with contents of 10, 15 and 20 kg/m(3) of concrete. The experimental program included diametral compression strength and water absorption tests. Twelve pipes were tested and divided into four sets of three pipes of nominal diameter (ND) of 600 mm and length of 1500 mm. Each series consisted of three pipes stub and bag (SB), one control (without rubber tires), and three sets incorporating rubber pipes on the trace (TB1, TB2 and TB3). All test results showed diametrical compressive strength values higher than that specified the NBR 8890 standard, with respect to simple concrete pipes PS2 class: type SB with ND 600 mm, which is 36 kN/m. In the water absorption test all pipes had absorption values less than the maximum established in the NBR 8890 standard, which is 8%. It can be concluded from the results and specific conditions of the tests conducted, that the tire rubber has the potential to be incorporated into the manufacture of simple concrete pipes. However, it is stated that it is necessary to increase the knowledge about the behavior of concretes incorporating rubber tire.
Keywords: Simple concrete pipes; rubber tires; diametral compression; water absorption